2003
DOI: 10.3168/jds.s0022-0302(03)73949-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipopolysaccharide on Indices of Peripheral and Hepatic Metabolism in Lactating Cows

Abstract: Four multiparous lactating cows (175 to 220 d in milk [DIM]) were used in a 4 x 4 Latin square design to assess the effects of four doses (0.0, 0.5, 1.0, and 1.5 microg/kg of body weight) of lipopolysaccharide (LPS; Escherichia coli 0111:B4) on performance and plasma metabolite and hormone concentrations. In addition, effects of immune activation on in vitro hepatic metabolic capacity were evaluated in 12 multiparous lactating cows (150 to 220 DIM) infused with 0 (n = 6), 1.0 (n = 4) or 2.0 (n = 2) microg of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
159
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(211 citation statements)
references
References 58 publications
44
159
8
Order By: Relevance
“…This increase in rectal temperature indicated that the LPS elicited a stress response. Similar increases in rectal temperature have been observed in response to LPS challenge in adult cattle (Waldron et al, 2003) and growing heifers 250kg weight (Waggoner et al, 2009a).…”
Section: Resultssupporting
confidence: 73%
“…This increase in rectal temperature indicated that the LPS elicited a stress response. Similar increases in rectal temperature have been observed in response to LPS challenge in adult cattle (Waldron et al, 2003) and growing heifers 250kg weight (Waggoner et al, 2009a).…”
Section: Resultssupporting
confidence: 73%
“…The previous studies showed that cytokines secreted by immune cells can activate the hypothalamic-pituitary-adrenal axis (HPA) after dairy cows were subjected to LPS injection (Steiger et al, 1999;Waldron et al, 2003). The results from Karrow et al (2010) also showed that sheep injected with interleukine-6 stimulated cortisol and corticotrophin hormone secretion into the peripheral circulating system, indicating a cross-talk of immune system and the HPA axis.…”
Section: Introductionmentioning
confidence: 76%
“…The goal to maintain plasma BHBA at 1.7 mmol/L through an increased BHBA infusion rate could not be achieved because the decline in plasma BHBA concentration was faster than the possible adjustment of infusion rate. Waldron et al (2003) suggested that the decline in plasma BHBA concentration was related to the suppression of ruminal epithelium ketogenesis capacity after LPS Figure 1. Mean BHBA infusion rate during −24 to −48 h of infusion (24-48h inf) and hourly after LPS challenge (510 min) in BHBA cows (HyperB; n = 5).…”
Section: Discussionmentioning
confidence: 98%